PUBLIC SERVICE ACCOUNTABILITY IN MANAGING SURAT IZIN MENDIRIKAN BANGUNAN (S-IMB) - Rike Yolanda Panjaiitan; Rike Yolanda Panjaiitan (JURNAL AKUNTANSI FINANCEIAL STIE SULTAN AGUNG, 2023)
The implementation of public service accountability is guided by the Decree of the Minister of State Number 63 of 2003 concerning General Guidelines for the Implementation of Public Services through Transparency and Accountability of Public Service Delivery, which contains the importance of providing public services. Licensing services in Medan City can be carried out at the Medan City DPMPTSP, one of the licensing services is the administration of Surat Izin Mendirikan Bangunan (S-IMB). The permit is still not in accordance with the Service Standards, which is for a period of 30 working days. One Stop Service and Investment Service for Medan City. The research method used is descriptive research method with a qualitative approach. Data collection techniques were carried out by means of interviews, observations, and documentation related to Surat Izin Mendirikan Bangunan (S-IMB). The data obtained were analyzed qualitatively by examining what had been collected using Sheila Elwood's Process Accountability theory which has the following indicators: Procedure, Cost, Timeframe and Responsiveness at the Medan City Investment and One-Stop Integrated Service Office, it has been running quite well but not yet optimal. There were several obstacles, such as permits not being completed on time, due to the lack of files from applications that were not submitted simultaneously to the officer. So that the incoming file must be returned to the applicant to complete the file and it takes a long time to complete the lack of files.